Alpha-ketoglutarate extends Drosophila lifespan by inhibiting mTOR and activating AMPK - Su, Yuan (Aging (Albany NY), 2019)
Alpha-ketoglutarate (AKG) is a key metabolite of the tricarboxylic acid (TCA) cycle, an essential process influencing the mitochondrial oxidative respiration rate. Recent studies have shown that dietary AKG reduces mTOR pathway activation by inhibiting ATP synthase, thereby extending the lifespan of nematodes. Although AKG also extends lifespan in fruit flies, the antiaging mechanisms of AKG in these organisms remain unclear. In the present study, we explored changes in gene expression associated with the extension of Drosophila lifespan mediated by dietary AKG. Supplementation of the flies’ diets with 5 μM AKG extended their lifespan but reduced their reproductive performance. Dietary AKG also enhanced vertical climbing ability, but did not protect against oxidative stress or increase tolerance to starvation. AKG-reared flies were resistant to heat stress and demonstrated higher expression of heat shock protein genes (Hsp22 and Hsp70) than control flies. In addition, AKG significantly upregulated mRNA expression of cry, FoxO, HNF4, p300, Sirt1 and AMPKα, and downregulated expression of HDAC4, PI3K, TORC, PGC, and SREBP. The metabolic effects of AKG supplementation included a reduction in the ATP/ADP ratio and increased autophagy. Collectively, these observations indicate that AKG extends Drosophila lifespan by activating AMPK signaling and inhibiting the mTOR pathway.